(untitled) (Journal of Dhaka National Medical College & Hospital, 2015)
The aim of this study was to determine mortality rates and identify associated causes and to notified top ten causes at a tertiary hospital situated in the Dhaka, Bangladesh. Death certificates from Dhaka National Medical Collage Hospital were retrieved and reviewed for the period 1st January to 31st December 2014 in this cross sectional study. Data were collected using a data collection form designed for the study. The average death rate was 6.8 deaths per 1000 patients based on the number of patients admitted during the study period. The age of the deceased ranged from 15-85 years, with a mean of 49.1 ± 18.6 years. Total number of death 74, where 30 (40.5%) are male, and 44 (59.5%) are female. Cardiovascular disease and diabetes mellitus, Chronic Kidney Disease (CKD), Chronic Obstructive Pulmonary Disease (COPD), Hepatic Encephalopathy, Acute Gastro Enteritis (AGE), Cancer (Bronchogenic carcinoma) and infection were the top 10 most common causes of death and were responsible for 61.2% of all recorded deaths. Cardiovascular diseases was the main cause of death. Overall the triple burden infectious diseases, non-communicable diseases (NCDs) and cancer remain the leading causes of death in patients at the study site. Interventions to control the spread of infectious diseases, cancer screening services and culturally appropriate lifestyle programs are urgently needed to address NCDs. J.Dhaka National Med. Coll. Hos. 2015; 21 (02): 55-57